Botanical extracts for insect management: Lessons from participatory research in peri-urban horticultural systems of central Argentina - Gaona Flores, Maria Amparo (2024)
We evaluate botanical insecticides as a technological device for synthetic input substitution in peri-urban horticultural system transitions. For that purpose, a Participatory Action Research (PAR) framework was proposed, and garlic extracts (GE) performance was evaluated for pest and natural enemy regulation in lettuce crops in conventional and agroecological contexts. Through three PAR cycles under actual production conditions, we observed GE effectiveness on aphids, thrips, and natural enemies. Additionally, context-specific adaptations were noticed: for conventional systems; the extract is useful near harvest and serves as a trust-building tool while reducing synthetic insecticide dependence. Instead, for agroecological systems, garlic extract highlighted biodiversity’s relevance for system redesign.